Hubungan Antara Disiplin Belajar Dan Motivasi Belajar Terhadap Hasil Belajar IPA Siswa Kelas V SDN 185 Bialo Kec. Gantarang Kab. Bulukumba - Aenun Jariatul Ubaidah; Evi Ristiana; Ma’ruf Ma’ruf (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
The formulation of the problem in this study is (1) whether there is a significant relationship between learning discipline and science learning outcomes of grade V students of SDN 185 Bialo; (2) whether there is a significant relationship between learning motivation and science learning outcomes of grade V students of SDN 185 Bialo, and; (3) whether there is a significant relationship between learning discipline and learning motivation on science learning outcomes of grade V students of SDN 185 Bialo.This type of research is correlational research, the sample in this study is 18 students of grade V SDN Bialo. The data collection techniques used are observation sheets, questionnaires, multiple-choice questions, and documentation. The data analysis technique used is descriptive quantitative analysis.The results showed that the learning discipline and motivation of grade V SDN Bialo had a significant positive influence on the learning outcomes of science students. From the results obtained, the correlation value between learning motivation and learning discipline of 0.978 is in the very strong correlation category with a significance value obtained smaller than 0.05, while learning motivation with learning outcomes of 0.524 is in the medium correlation category with a significance value smaller than 0.05.Based on the results of the research mentioned above, it can be concluded that the learning discipline and motivation of class V SDN Bialo has a significant positive influence on the learning outcomes of science students.